2018
DOI: 10.1021/jacs.8b04818
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Magnetodielectric Effect in a Dysprosium-Based Single-Molecule Magnet

Abstract: Materials that possess coupled magnetic and electric properties are of significant interest because of their potential use in next-generation magnetoelectric devices such as digital information storage. To date, the magnetoelectric materials that have been studied in-depth have been limited mainly to inorganic oxides such as perovskite oxides. Molecular materials are a promising alternative because their magnetic and electric elements can be combined together at the molecular level via relatively simple molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 46 publications
1
62
2
Order By: Relevance
“…Among the known single-phase compounds exhibiting isothermal magnetodielectric effects, the MD of PEA-Mn is smaller than those of the outstanding inorganic oxides such as TbMnO 3 ( ref. 5 ) and DyMnO 3 , 14 is comparable with those of BiMnO 3 and a dysprosium-based single-molecule magnet, 6 , 30 and is much larger than those of Mn 3 O 4 , 43 TbFe 3 (BO 3 ) 4 ( ref. 44 ) and the metal–formate framework [(CH 3 ) 2 NH 2 ][Fe(HCOO) 3 ].…”
Section: Resultsmentioning
confidence: 89%
“…Among the known single-phase compounds exhibiting isothermal magnetodielectric effects, the MD of PEA-Mn is smaller than those of the outstanding inorganic oxides such as TbMnO 3 ( ref. 5 ) and DyMnO 3 , 14 is comparable with those of BiMnO 3 and a dysprosium-based single-molecule magnet, 6 , 30 and is much larger than those of Mn 3 O 4 , 43 TbFe 3 (BO 3 ) 4 ( ref. 44 ) and the metal–formate framework [(CH 3 ) 2 NH 2 ][Fe(HCOO) 3 ].…”
Section: Resultsmentioning
confidence: 89%
“…The known mer-LnBr 3 (OPcy 3 ) 3 (mer ¼ meridional; cy ¼ cyclohexyl, C 6 H 11 ) have been recently reported and give opportunity for extension to the trivalent actinides, though small lanthanides can speciate. 57,[64][65][66] There has been just one report of a single crystal Am-Br compound, AmBr 3 (THF) 4 . 67 The previously reported syntheses of mer-LnBr 3 (OPcy) 3 , (cy ¼ cyclohexyl, C 6 H 11 ) utilized boiling ethanol and describe the complexes as having low solubility.…”
Section: Synthesismentioning
confidence: 99%
“…[1][2][3] Comparing with transition metal ions, lanthanide (Ln) ions oen possess large orbital angular momentum and inherent magnetic anisotropy, which contribute to improving the effective energy barrier (U eff ) and blocking temperature (T B ) of SMM materials. [4][5][6][7] As a result, Ln ions particularly Dy(III) ion have become ideal candidates to construct SMM materials since Ishikawa et al reported the rst Ln-based SMM of [Pc 2 Ln] À $TBA + (Ln ¼ Tb or Dy, Pc ¼ dianion of phthalocyanine; TBA + ¼ N(C 4 H 9 ) 4 + ) in 2003. 8 Aer that, numerous Ln-based SMM materials including discrete Ln x (x $ 1) coordination clusters, chainlike, two dimensional and three dimensional coordination compounds have been prepared and investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we report two polyhydroxylamine-derived Schiff-base {Dy 2 }-based one dimensional chain compounds {[Dy 2 (H 3 L) 4 (OAc) 6 ]$2MeOH} n (1) and {[Dy 2 (H 3 L) 4 (OAc) 4 (NCS) 2 ]$ 2MeOH} n (2) featuring with similar structures. The different coordination groups of Dy(III) in 1 and 2 lead to different geometrical congurations and symmetries and coordination numbers of Dy(III) ions.…”
Section: Introductionmentioning
confidence: 99%